Enjoying motherhood / Tengku Elena Tengku Mahamad - Tengku Mahamad, Dr. Tengku Elena (Universiti Teknologi MARA Cawangan Kedah, 2022)
A compilation of poems from interested 118 lecturers and academicians from UiTM and other higher learning institutions.